PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SUKA FAJAR PEKANBARU - Syafrina, Nova (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
This study aims to determine the effect of work discipline on employee performance at PT. Suka Fajar Pekanbaru. Population in this research all employees of PT. Suka Fajar Pekanbaru which amounted to 32 people. Because the population is relatively few and less than 100 people, the sampling technique in this study using saturated sampling. Where all members of the population are sampled. So the sample in this study is 32 employees of PT. Suka Fajar Pekanbaru .. Data analysis methods used are reliability test, and coefficient of determination. While the hypothesis test used simple linear regression test and t test. The result of this research is that there is a significant influence between work discipline on employee performance at PT. Suka Fajar Pekanbaru. With the provision t arithmetic greater than t table